Strategi Peningkatan Animo Masyarakat Melalui Digital Marketing Dalam Penerimaan Peserta Didik Baru Di Sekolah Dasar Mutiara Bali Tahun Pelajaran 2020/2021 - Samirah, Ayu; Jumari, Jumari; Khoeron, Khoeron (STAI Denpasar Bali, 2021)
The background of this research is because of the school that is very active in implementing digital marketing systems by utilizing social media that exists at this time, one of the supporters who provides a variety of information is quite in the grasp and as an information media that can also expand its reach so that it can attract the interest of the surrounding community. The focus of research is as follows: 1) How is the strategy to increase public interest through digital marketing in the acceptance of new learners in SD Mutiara Bali in the 2020/2021 school year?, 2) What are the obstacle factors and solutions in the strategy of increasing public interest related to the acceptance of new learners in Mutiara Bali Elementary School in the 2020/2021 school year. The purpose of the research is to find out 1) strategies to increase public interest through digital marketing in the acceptance of new learners in SD Mutiara Bali in the 2020/2021 school year, 2) obstacle factors and solutions in the strategy of increasing public interest related to the acceptance of new learners in SD Mutiara Bali in the 2020/2021 school year. This type of research uses a qualitative approach. Data collection includes observations, interviews and documentation. Based on the results of research that has been obtained by researchers, that from the beginning of the establishment of SD Mutiara Bali has been actively using digital marketing system and is known based on data that SD Mutiara Bali has indeed experienced an increase in public interest from year to year with various strategies carried out such as branding, content creator well then published through social media owned by SD Mutiara Bali.